(untitled) (Research, Society and Development, 2021)
Introduction: Primary health care presents itself as the main gateway to the health system, therefore, it is expected that the demands of mental health can also be welcomed, forwarded, monitored and often treated by professionals who work in this service. Objective: To verify scientific evidence based on evidence regarding mental health care in primary health care. Methodology: The search for scientific articles was conducted by two independent researchers in the databases Medline (Pubmed), LILACS, SciELO, Bireme, Web of Science and Scopus, without restriction of language, period and location. Studies that scored ≥ 6 points according to the qualitative scoring protocol proposed by Pithon et al. (2015). Results: The admitted studies point to patients who obtained mental health care only from the primary care physician, as well as feedback assessment found the applications useful. Twenty-four (68.5%) of the patients reported using Breathe2Relax and 24 (68.5%) reported using self-help for Anxiety Management. Conclusion: A greater focus on patient-centered care requires greater integration between primary care and the mental health sector so that there is a reduction in the fragmentation of care and disparities in health outcomes. Mental health-related applications are applicable and relevant to patients in integrated primary care environments in safety net health systems.